Modern Sufis and the State The Politics of Islam in South Asia and Beyond - Ewing, Katherine Pratt; Corbett, Rosemary R. (New York Columbia University Press, 2020)
In recent years, Sufism has been held up as a supposedly peaceful alternative to forms of Islam associated with violence, an embodiment of tolerance and pluralism. Modern Sufism and the State brings together a range of scholars, including anthropologists, historians, and religious-studies specialists, to challenge common assumptions.
Intro -- Table of Contents -- Acknowledgments -- Note on Transliteration -- Introduction: Sufis and the State: The Politics of Islam in South Asia and Beyond, by Katherine Pratt Ewing -- Part I: Sufism and Its Modern Engagements with a Global Order -- 1. Anti-Colonial Militants or Liberal Peace Activists? The Role of Private Foundations in Producing Pacifist Sufis During the Cold War, by Rosemary R. Corbett -- 2. From Taṣawwuf Modern to Neo-Sufism: Nurcholish Madjid, Fazlur Rahman, and the Development of an Idea, by Verena Meyer -- 3. Beyond Barelwiism: Tahir-ul-Qadri as an Example of Trends in Global Sufism, by Marcia Hermansen Commentary on Part I: Ambiguities and Ironic Reversals in the Categorization of Sufism, by Carl W. Ernst -- Commentary on Part I: Ambiguities and Ironic Reversals in the Categorization of Sufism, by Carl W. Ernst -- Part II: Sufis, Sharia, and Reform -- 4. Is the Taliban Anti-Sufi? Deobandi Discourses on Sufism in Contemporary Pakistan, by Brannon D. Ingram -- 5. Sufism Through the Prism of Sharia: A Reformist Barelwi Girls' Madrasa in Uttar Pradesh, India, by Usha Sanyal -- 6. Lives of a Fatwa: Sufism, Music, and Islamic Reform in Kachchh, Gujarat, by Brian E. Bond -- Commentary on Part II:Sufis, Sharia, and Reform, by Muhammad Qasim Zaman -- Part III: Sufis and Politics in Pakistan -- 7. "A Way of Life Rather Than an Ideology?": Sufism, Pīrs, and the Politics of Identity in Sindh, by Sarah Ansari -- 8. Sufi Politics and the War on Terror in Pakistan: Looking for an Alternative to Radical Islamism?, by Alix Philippon -- 9. "Our Vanished Lady": Memory, Ritual, and Shiʿi-Sunni Relations at Bībī Pāk Dāman, by Noor Zaidi -- Commentary on Part III: The Problems and Perils of Translating Sufism as "Moderate Islam," by SherAli Tareen -- Part IV: Sufism in Indian National Spaces.
Description based on publisher supplied metadata and other sources
Keywords: Sufis-Political activity-South Asia; Electronic books